HUBUNGAN EXPLOSIVE POWER OTOT LENGAN DAN BAHU DENGAN HASIL PUKULAN FOREHAND SMASH BULUTANGKIS PADA SISWA PUTRA KELAS X MIA 1 SMAN 8 PEKANBARU - Firman Hidayat; Slamet '; Yuherdi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study was conducted to determine whether there is a relationship of explosive power arm and shoulder muscles with a forehand smash badminton results in grade male student SMAN 8 x mia 1 Pekanbaru, so when doing a good forehand smash. Shape of the research is the correlation, the population in this study were students SMAN 8 Pekanbaru. The sample in this study were male students class X mia SMAN 8 pekanbaru as many as 14 people. A sampling technique the whole population (total sample). The instruments used in this study is two-Hand put medicine ball test, which is designed to measure the strength of the arm and shoulder muscles than testing forehand smash badminton. Then the data is processed with statistics, normality test lilifors test at significant level 0,05α. The hypothesis is suspected, there is a significant relationship between the explosive power arm and shoulder muscles with the results of a forehand smash at grade male student x mia 1 SMAN 8 Pekanbaru. On the basis of the test analysis lilifors produce Lhitung (x) of 0.15 and 0.227 Ltabel, Lhitung (y) of 0.12 and 0.227 Ltabel means Lhitung <Ltabel, than the samples come from normal berdristribusi population. Then the calculation of the product moment correlation between the explosive power arm and shoulder muscles with the obtained javelin rhitung 0,581 and 0.553 rtabel results mean rhitung <rtabel so Ho rejected and Ha accepted. So there is a significant correlation between the explosive power arm and shoulder muscles with a forehand smash badminton results in grade male student x mia 1 SMAN 8 Pekanbaru.Keywords: explosive power arm and shoulder muscles, forehand smash badminton2HUBUNGAN